MAKING EDUCATIONAL VIDEOS USING ANIMATION TECHNIQUES FOR ELEMENTARY SCHOOL STUDENTS - Asrul Sani (Adisam Publisher, 2024)
The use of technology in education has now become an effective method for increasing students' interest and understanding of subject matter. This research aims to develop learning materials through making educational videos using animation techniques, which are designed specifically for students. The animation method was chosen because of its unique ability to present abstract concepts more easily understood and interesting for students. This research includes the design process, content development, animation, and evaluating the effectiveness of the educational videos that have been created. The approach used in this research is development (Research and Development) which involves students as respondents to determine their level of understanding and interest in the material presented through animated educational videos. The educational videos developed cover various learning topics that are adapted to the applicable curriculum, with the hope that they can become an interesting additional learning resource and increase students' understanding. The research results show that educational videos using animation techniques are able to increase students' interest in learning and make it easier for them to understand lesson concepts that were previously considered difficult. Evaluations carried out through questionnaires and interviews showed positive responses from students towards the use of this learning media. Thus, it is hoped that making animation-based educational videos can be an effective alternative learning method and can be applied in various educational contexts.